JARINGAN SOSIAL PRODUSEN BERAS DI DESA LERAN KULON KECAMATAN PALANG KABUPATEN TUBAN - Aprillia, Mita (Paradigma, 2022)
The number of rice producers in Leran Kulon Village is quite a lot, namely 78, making rice producers must have a good network to maintain their business. This study explains how social networks occur in rice producers in Leran Kulon Village so that their business can run until now. The purpose of this study is to describe the actors or actors involved in the social network, analyze the form of the social network, and describe the role of each actor involved in the social network. This study uses a qualitative method with the social capital theory of Coleman and Putnam as the analysis. Collecting data in this study using observation techniques, structured interviews and secondary data. The results of this study indicate that; First, the actors involved in the social network of rice producers in Leran Kulon Village, namely farmers, rice producers, rice middlemen (grain), distributors and consumers. Second, the form of social networks in the social network of rice producers is divided into two, namely trust-based and kinship-based. Trust-based social networks can be seen from the relationship between rice middlemen and rice producers, in addition to the relationship between rice producers and distributors. The kinship-based social network can be seen from the kinship relationship that occurs between farmers and rice producers in the sale of grain. Keywords: Rice Producer, Social Network, Trust, Kinship